The role of normativity and rationality in establishing mental anomalism - Brink, Claudi (My University, 2012)
In this paper I argue that the thesis of nomological irreducibility that Davidson aims to establish in Mental Events cannot be understood without taking into consideration the central role that the constitutive ideal of rationality plays in his thinking about the nature of the mental. My aim is to investigate in more detail the conception of rationality that Davidson thinks plays an essential role in psychological theorizing. I suggest that the regulatory role of the feature of rationality, that is an essential one of the mental, bestows on mental concepts and the explanations in which they feature, an essential normative character. Such normativity depends on the fact that the concepts are necessarily ceteris paribus in the sense that the conditions that limit the application of the concepts aren’t exhaustively enumerable in any vocabulary. This undermines the possibility of formulating strict laws. Strict laws require that we are able to fully explicate the conditions that limit the application of the concepts it employs. Such exhaustive enumeration is possible only in the vocabulary of a closed theory, namely, physics. As soon as we change the vocabulary from mental to physical in order to fully explicate the clauses we can no longer recognize the events we describe to be mental ones. This change of subject is the result of the fact that we can no longer recognize the concepts to answer to a standard that is an ideal, namely, rationality.
M.A. University of the Witwatersrand, Faculty of Humanities (Philosophy), 2012